Privacy Enhanced Web Search Using MKSE in KNN - Sumathi, R; Geetha, V (International Journal of Computer Sciences and Engineering, 2025)
Customized Web Look has established to make strides the quality of different look administrations on the Internet. Due to tremendous data opportunities in the internet, the security assurance is exceptionally critical to preserve customer look behaviors and their profiles. In the existing framework the summed up calculation specifically Covetous DP calculation were connected to secure private data’s in modified look engine. The existing frame lives up to expectations failed to resist successive and foundation information adversaries who has the broader foundation information such as richer relationship among topics. The proposed framework introduces vector that point again quantization approach piecewise on the datasets which segmented each column of datasets and that quantization approach is performed on each segment, utilizing the proposed approach which later is again united to structure a transformed data set. The proposed work is implemented and is analyzed utilizing certain parameters such as Precision, Recall, Frequency Measure, Distortion and Computational Delay.